An Investigation of Classroom Management Strategy ( A Case Study of Tenth Grade English Teachers at SMAN 2 Kota Bengkulu) - Dona Novianti Ulfa; Rudi Afriazi; Elfrida . (Universitas Bengkulu, 2019)
The objective of this research was to find out the classroom management strategies implemented by the English teachers and the reason in applying the most often strategy than others strategies. This study employed the descriptive qualitative method, the subject of the research were the English teachers (2 persons) at SMAN 2 Kota Bengkulu.. The data was collected by using observations checklist and interview. The result of the research revealed there are 5 strategies used by the teachers in managing the classroom; 1) Strategies to arrange the classroom, 2) Strategies to build positive relation with the student, 3) Strategies to create positive classroom environment, 4) Strategies to prevent misbehavior and5) Strategies to handle the students’ discipline situation. In 5 meetings the total aspects of the first strategy applied by the teacher 1 and teacher 2 was about 33 and 37. The second strategy was 30 and 31. The third strategy was 26 and 24. The fourth strategy was 25 and 28. The last strategy was 25 and 24. Furthermore, the reasons of why the teachers applying the most often strategy than others strategies because it helps the teachers in the teaching and learning process to be more conducive. Beside that the strategies also help the teachers to create an effective teaching and learning process. Therefore, it could be concluded that the English teachers of SMAN 2 Kota Bengkulu used all the 5 strategies asmentioned by Marzano (2003) in managing classroom but not all aspects they used in teaching and learning process. The dominant strategy implemented by Teacher I and Teacher 2 were strategy to arrange the classroom. Meanwhile, the least strategy implemented by both teachers were the strategy to handle the students discipline situation.